Perceptually adaptive graphics - MCDONNELL, RACHEL; O'SULLIVAN, CAROL ANN (My University, 2004)
In recent years, the Graphics community has come to realise the importance of taking human perception into account when striving for realism in images, animations and Virtual Environments. In May 2001, a EUROGRAPHICS/ SIGGRAPH Campfire brought together a group of researchers from various fields, including computer graphics and visualisation, psychology, neuroscience, eye-movements and medicine to discuss the future and current state of the field. Since then, many researchers have been very active in furthering the field of perceptually adaptive graphics. In this report, we outline the state of the art as discussed at that event and the progress that has been made since.
PUBLISHED
Keywords: Perceptual Metrics; Psychophysics